THE EFFECT OF TAX AVOIDANCE, PROFITABILITY, LEVERAGE, AND COMPANY SIZE ON EARNINGS MANAGEMENT - Halim, Caroline Maretha; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2025)
Companies frequently use earnings management to falsify financial figures in order to accomplish specific goals. Numerous financial and operational elements, such as tax evasion, profitability, leverage, and firm size, might have an impact on this activity. The purpose of this study is to look at how these factors affect profits management in consumer goods businesses that are not cyclical and are listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The research employs a purposive non-probability sampling method, resulting in a final sample of 127 data from 31 companies. The associations between variables are examined applying multiple linear regression analysis. The findings reveal that corporate size and leverage significantly impact earnings management. This suggests that businesses with more debt are more likely to manipulate earnings, possibly in order to satisfy debt covenants or enhance their financial soundness in the eyes of creditors. Larger companies may also be more likely to strategically modify their earnings due to their greater resources and regulatory scrutiny. Profitability and tax evasion, however, have little bearing on profits management. This suggests that efficiency, not opportunistic earnings manipulation, is the main reason why company tax planning tactics are used. Likewise, highly profitable firms may not feel pressured to alter reported earnings, as their financial performance is already strong. These results provide valuable insights for regulators, investors, and policymakers in understanding corporate financial behavior and enhancing transparency in financial reporting.